That uncertain feeling = Ehekomödie - Najac, Émile de 1828-1889; Sardou, Victorien 1831-1908; Stewart, Donald Ogden 1894-1980; Heymann, Werner Richard 1896-1961 (MVD Visual, 2020)
After visiting a psychoanalyst to treat her psychosomatic hiccups, a woman becomes disenchanted with her husband and develops a relationship with a pianist as her husband tries to win her back
Bonus: Castle films news parade of 1941; Daffy Duck in Henpecked Duck (1941)
Spielfilm, Orig.: USA, 1941
PCM mono, full screen 1.37:1
Keywords: Filmkomödie; Verfilmung; Man-woman relationships / Drama; Marriage / Drama; Sardou, Victorien / 1831-1908 / Film adaptations; Sardou, Victorien / 1831-1908; Man-woman relationships; Marriage; screwball comedy; Video recordings for the hearing impaired; Screwball comedy films; Fiction films; Feature films; Comedy films; Drama; Film adaptations; Comédies loufoques (Films); Films comiques; Adaptations cinématographiques; Films de fiction; Vidéos pour personnes handicapées auditives; Film; DVD-Video